Survey on Data Security and Privacy Preserving in Big Data - A.Vineela, A.; Kasiviswanath, N.; Sudha Ran, L. (International Journal of Engineering and Technology, 2018)
With the rapid growth of IT industry, big data needs the improvement in storage, computation and network field. This enhancement also brings the new security and privacy issues to the big data. The researchers are attracted towards to solve the security and privacy issues. This paper made a survey on characteristics of big data along with security issues. The traditional security methods of cloud computing are not appropriate to the big data. Privacy preserving is also one major issue in big data. This survey also provides complete study on research issues and challenges of privacy preserving and the comparison is made to the privacy preserving techniques. Finally, this paper provides comprehensive overview of the methods to solve the big data security problem.